2017
DOI: 10.1902/jop.2016.160453
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Non‐Impacted Third Molars on Pathologies of Adjacent Second Molars: A Retrospective Study

Abstract: Presence of N-M3s, even if they are asymptomatic, represents an important risk factor for periodontal health of A-M2s. This finding should be considered during clinical decision making regarding retention or extraction of N-M3s, especially when these teeth are non-functional or when their removal will not affect overall occlusal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 36 publications
2
33
0
3
Order By: Relevance
“…Both impacted and nonimpacted M3 have been associated with localized periodontitis at M2. 23,36,37 The elevated proportions of subgingival periodontopathogens at M2/M3 deep pockets may be responsible for disease persistence and are key risk factors for the progression of periodontal disease. 17,38,39 Within the limitations of our study, multiple logistic regression analysis has shown in the present study that history of periodontitis, preoperative deep pockets, and older age are independent risk factors for poorer healing and residual pockets postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Both impacted and nonimpacted M3 have been associated with localized periodontitis at M2. 23,36,37 The elevated proportions of subgingival periodontopathogens at M2/M3 deep pockets may be responsible for disease persistence and are key risk factors for the progression of periodontal disease. 17,38,39 Within the limitations of our study, multiple logistic regression analysis has shown in the present study that history of periodontitis, preoperative deep pockets, and older age are independent risk factors for poorer healing and residual pockets postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the attention paid to the negative impacts of asymptomatic I‐M3s on oral health, the influence of N‐M3s on the health of neighboring teeth has also gained increasing attention from dentists in recent years (Chou, Ho, Ho, Wang, & Hu, 2017; Li, Qu, Zhou, Tian, & Chen, 2017; Li, Qu, Zhou, Tian, Gao, et al, 2017). Based on previous data, the presence of N‐M3s may increase the risk of pathology in M2s; specifically, the risk of periodontal damage in M2s with the presence of N‐M3s was found to be 1.45–6.79 times higher than that of M2s without neighboring M3s (Kindler et al, 2018; Li, Qu, Zhou, Tian, & Chen, 2017; Li, Qu, Zhou, Tian, Gao, et al, 2017; Nunn et al, 2013; Qu et al, 2017). Consistent with these previous studies, our study also confirmed that the presence of N‐M3s increased the risk of periodontal destruction in their adjacent M2s, and the PD5+ risk in M2s adjacent to N‐M3s was 2.58‐fold higher than that in M2s without neighboring M3s (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Among the total population, subjects with mandibular erupted third molars (most likely N‐M3s) had a higher risk of deep PD values in their adjacent M2s than those without M3s (Kindler et al, 2018). On the other hand, a cross‐sectional study based on radiological data of 4,057 patients showed that the prevalence of alveolar bone loss in the distal M2s adjacent to N‐M3s was 40.4%, which was similar to that of M2s adjacent to I‐M3s (41.5%; Li, Qu, Zhou, Tian, & Chen, 2017). These data suggest that N‐M3s, similar to I‐M3s, are associated with an increased risk of M2 pathology.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…1 However, the decision of extracting or maintaining a third molar is controversial. 2 If an impacted third molar is not extracted after a certain stage of its formation, it may contribute to second molar ERR. 1 According to Tsesis et al 3 ERR is a pathological process that occurs at the permanent tooth outer surface and it may be induced by pulpal infection or periodontal inflammation related causes, or pressure associated with orthodontic movements, impacted tooth or pathoses.…”
Section: Introductionmentioning
confidence: 99%